Prebiótico e probiótico na dieta de tilápia-do-Nilo: perfil hematológico, resposta imune inata e desempenho zootécnico - Oshiro, Eliana [UNESP] (2015)
This study aimed to evaluate the growth performance, corporal composition, haematological parameters, innate immune response, resistance against the experimental infection with Aeromonas hydrophila and confirm the presence of probiotic bacteria in the intestines of Nile tilapia, Oreochromis niloticus, fed with addition of prebiotics Actigen® MOS - MOS (P1), Kappaphycus alvarezii seaweed (P2), and PAS-TR® probiotic composed of Bacillus cereus and Bacillus subtilis (P). The additives were tested separately and in combination (S1 = PAS-TR® + MOS and S2 = PAS-TR® + K. alvarezii). One group was fed with control diet (C). The experiment was divided into two stages. In the first stage, 240 juveniles, with initial average weight of 8.86 ± 3.22g, distributed in a completely randomized design of 6 treatments and 4 replications were fed with the specific diets for 63 days. In the second stage, the feeding period was 21 days and the 180 animals were experimentally infected with Aeromonas hydrophila on the 22nd day. The observation of mortality rates period was 15 days post-infection. There were no statistical differences (p> 0.05) on performance, corporal composition, haematological and immunological parameters. It was possible to recover the probiotic bacteria in the intestinal tract of exemplary fed with diets containing added probiotics. The fish treated with immunostimulants presented better survival rates (p <0.05) compared to the control group when challenged with A. hydrophila, confirming the feasibility of including these in the diet